Editorial - González-Campo, Carlos Hernán (Cuadernos de Administración, 2018)
Issue 61 of the Journal Cuadernos de Administración publishes 7 papers on the different topics of editorial interest, which national and international authors have considered disseminating in our publication, and which have been selected after a rigorous assessment process. The first paper, entitled “The use of social media to improve the commitment of stakeholders in the fashion and clothing sector: the Inditex case”, is the result of a research wherein, by means of a descriptive analysis, the different levels of participation in Facebook and the main characteristics that stimulate such participation in Inditex are studied. “Strategy and generation of value in Colombian service companies”, is the title of our second paper, the result of research aimed at identifying the relationship between strategy and value generation in service companies that have won the Colombian Management Quality Award by the Ministry of Commerce, Industry and Tourism in the period 2013-2014. Innovation in Companies operating in the Foodstuffs Sector of Colombia. An analysis from the perspective of open innovation”, is the third paper and the result of a qualitative study that investigates the characteristics of the actors and their relationships in four areas of the foodstuffs sector in Colombia (the meat, dairy, milling and confectionery sectors). “Environmental entrepreneurship and public policy. Case: Entrepreneurship for Life Program”, is the title of the fourth paper in this issue, in which the authors, using the methodology of the Synergy System, applied by the Colombian Government to evaluate public policies, evaluate the “Entrepreneurship for Life” program. The fifth paper “Formal and informal institutions in relation to the entrepreneurial phenomenon in the Americas”, presents the results of a study that analyses the impact of formal and informal institutions on the change of the entrepreneurial activity rate (TEA) in 9 countries in the Americas, using data from GEM studies between 2005 and 2015. “Global communication models and their importance to public administrations - the case of the Secretariat of Information and Communication Technologies in Cundinamarca” is the title of the sixth paper published herein, and is the result of a study on the state of communications in the process of collecting requirements between the Secretariat of Information and Communication Technologies, the Government of Cundinamarca and the municipalities of the department through surveys and interviews with stakeholders and comparative analysis based on the current technical quality standards and variables of the global communication model. At the end of this issue, a review article entitled “Do social media create long-term brand experiences?” is published, in which the authors present a series of questions on the problem of the relationship between social networks and brand experience within marketing strategies. The article defines several lines wherefrom to outline future research. From the editorial team, we thank all the authors of this issue of the Journal Cuadernos de Administración for their contributions and our readers. We hope that all the changes that are being made as a journal will enable greater diffusion of published knowledge, where its content is the exclusive responsibility of each author and does not compromise the Faculty of Administrative Sciences of the Universidad del Valle, as the publishing entity.